The category of contemporary social theory - Matsevich-Dukhan, Iryna Ja. (Journal of the Belarusian State University. Sociology, 2019)
The article reveals different approaches to defining the notion «social theory». Its development within the social and human sciences is traced. Its further transformation into one of the key categories of socio-philosophical cognition is delineated. Regional differences in interpretations of this category are indicated. Reasons for the emergence of the universal category of social theory at the turn of XX–XXI centuries are outlined.
Keywords: social theory; sociological theory; socio-philosophical theory; theory of society; contemporary social theory